Study on the metabolic effects of hexavalent chromium [Cr (VI)] on rat astrocytes using un-targeted metabolomics - Tang, Hongge; Li, Kunyang; Lin, Lin; Wang, Wenying; Jian, Wenjie (Frontiers in Molecular Biosciences, 2024)
Introduction: Hexavalent chromium [Cr (VI)] has been identified as a human carcinogen and environmental pollutant capable of affecting multiple systems in the human body. However, the specific mechanisms by which Cr (VI) affects the human nervous system remain unclear. Objective: Following confirmation of Cr (VI)’s toxic effects on rat astrocytes, this study explores the metabolites and associated metabolic pathways of rat astrocytes under different doses of Cr (VI) exposure. Methods: Cell viability was assessed using CCK8 assays, intracellular reactive oxygen species (ROS) levels were measured using DCFH-DA fluorescent probes, intracellular 8-hydroxydeoxyguanosine (8-OHdG) content was determined by Elisa, mitochondrial membrane potential was observed using JC-1 probes, and key metabolites were identified through untargeted metabolomics analysis. Results: With increasing Cr (VI) doses, significant decreases in cell viability were observed in the 4, 8, and 16 mg/L dose groups (p < 0.05). Elevated levels of ROS and 8-OHdG, increased caspase-3 activity, and significant reductions in mitochondrial membrane potential were observed in the 2 and 4 mg/L dose groups (p < 0.05). Untargeted metabolomics analysis revealed Cr (VI)’s impact on key metabolites such as sphingosine and methionine. Enrichment analysis of KEGG pathways highlighted the critical roles of sphingolipid metabolism and the methionine-cysteine cycle in the effects of Cr (VI) on rat astrocytes. Conclusion: Our study underscores the potential neuro-health risks associated with environmental and occupational exposure to Cr (VI) and provides new perspectives and directions for investigating neurotoxic mechanisms.